2021
DOI: 10.3390/cancers13164142
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Multifaceted Roles of Heme in the Pathogenesis of Cancer and Related Diseases

Abstract: Heme is an essential prosthetic group in proteins and enzymes involved in oxygen utilization and metabolism. Heme also plays versatile and fascinating roles in regulating fundamental biological processes, ranging from aerobic respiration to drug metabolism. Increasing experimental and epidemiological data have shown that altered heme homeostasis accelerates the development and progression of common diseases, including various cancers, diabetes, vascular diseases, and Alzheimer’s disease. The effects of heme on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 334 publications
(457 reference statements)
0
9
0
Order By: Relevance
“…Heme, a recognized molecular sensor 15 , contributes - perhaps via a paracrine/autocrine mechanism, - to the regulation of genes associated with biological processes as diverse as angiogenesis, oxidative stress management, circadian rhythm adjustment 90 , and anabolism 15 . Clearly, this recognition of heme as a signaling molecule has bolstered our understanding of the multifaceted roles of heme in cancer pathogenesis 91,92 . Our findings provide a new line of evidence for the signaling power of heme/porphyrin, particularly in relation to cellular redox stress and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Heme, a recognized molecular sensor 15 , contributes - perhaps via a paracrine/autocrine mechanism, - to the regulation of genes associated with biological processes as diverse as angiogenesis, oxidative stress management, circadian rhythm adjustment 90 , and anabolism 15 . Clearly, this recognition of heme as a signaling molecule has bolstered our understanding of the multifaceted roles of heme in cancer pathogenesis 91,92 . Our findings provide a new line of evidence for the signaling power of heme/porphyrin, particularly in relation to cellular redox stress and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Heme manifests its influence on biological processes by acting as a prosthetic group for, e.g., proteins of the cytb5 domain family (including MAPR proteins like PGRMC1), other cytochromes (e.g., CYP450s) and their reductases, kinases, transcription activating factors, transcriptional repressors, ion channels, miRNA processing proteins, and globins, which together act as electron carriers for the enzymatic oxidation or reduction of substrates, mediate oxygen sensing, gas synthesis (e.g., CO), transcriptional regulation, iron homeostasis, oxidative stress response, mitochondrial biogenesis, circadian rhythms, or influence cell cycle progression and proliferation. The latter are of course directly critical to disease [78,[80][81][82].…”
Section: Mapr Tyrosinate Heme Chelationmentioning
confidence: 99%
“…PGRMC1 knockdown promotes the differentiation of human pluripotential stem cells coincidentally with a reduction in autophagy and elevated activity of the p53 and Wnt/β-catenin pathways, which leads to loss of pluripotency and the differentiation into multiple cell types [140], consistent with a central role of autophagy and metabolism in maintenance of the autonomous single celled/stem cell state, which may reflect metabolic changes which permitted the evolution of the gastrulation organizer and therefore the LEUMCA. Note that p53 is also a heme-dependent protein [80,81], which could therefore also be targeted by PGRMC nuclear heme shuttling [82] independently of Wnt signaling.…”
Section: Potential Early Eukaryotic Mapr Functions Deduced From Moder...mentioning
confidence: 99%
“…There is mounting support for the hypothesis that a positive correlation exists between high levels of SQLE expression and a dismal prognosis in a variety of tumor types [ 31 ]. CBS is a pyridoxal 50-phosphate (PLP) enzyme that catalyzes the conversion of homocysteine (Hcy) and serine into cysteine by the transsulfuration pathway and regulates the metabolism of hydrogen sulfide (H 2 S), with higher H 2 S levels related to the proliferation of multiple tumor types [ 32 ]. In this study, the expression levels of these genes were shown to be elevated in UCEC tissues and had an unfavorable association with patients' prognoses.…”
Section: Discussionmentioning
confidence: 99%